The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/jocn.12229
|View full text |Cite
|
Sign up to set email alerts
|

The validation and application of the Chinese version of perceived nursing work environment scale

Abstract: Shaping nursing practice environments to promote desired outcomes requires valid and reliable measures to assess practice environments prior to, during and following efforts to implement change. The C-PNWE scale can be a useful measurement tool for administrators to improve the nursing work environment in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Each survey instrument selected has undergone this process in a broad range of acute healthcare environments internationally including Australia [100] , Brazil [42] , China [101] , Japan [102] , Spain [103] , the United Kingdom [31] , United States [104] and multi-nationally [105] . A summary of the psychometric assessment for the NWI-R, PES-NWI and MBI is provided in Table 2.…”
Section: Discussion and Instrument Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each survey instrument selected has undergone this process in a broad range of acute healthcare environments internationally including Australia [100] , Brazil [42] , China [101] , Japan [102] , Spain [103] , the United Kingdom [31] , United States [104] and multi-nationally [105] . A summary of the psychometric assessment for the NWI-R, PES-NWI and MBI is provided in Table 2.…”
Section: Discussion and Instrument Selectionmentioning
confidence: 99%
“…Australian study by Parker et al (2010) [100] , the construct validity and reliability of the PES-NWI was tested in a random sample of 3,000 nurses working in private and public sectors demonstrating strong internal consistency with a Cronbach alpha of 0.948. The study concluded that the PES-NWI is a reliable survey instrument for a range of clinical settings with ongoing refinement and testing based on large nursing populations underpinning its construct validity and reliability for the assessment of nurses work environment in acute care and ICU settings.…”
Section: Nurse Outcome Measuredmentioning
confidence: 99%
See 1 more Smart Citation
“…This is so while service sections have a remarkable role in economic growth and higher quality of individuals' life standards and the development of other sections would be impossible without considering service sections (Büyüközkan, Çifçi, & Güleryüz, 2011). Nurses are the largest group of professional employees in health care services who offer care directly to patients and their job conditions influence the consequences related to patients (Zhao et al, 2013). The psychological or mental pressure that is imposed on an individual due to job dissatisfaction can make him/her vulnerable, open and prone to diseases such as heart attack (Almalki, FitzGerald, & Clark, 2012).…”
Section: Introductionmentioning
confidence: 99%